Top-Rem grinding tool modification considering loaded edge contact for spiral bevel gears. (August 2022) - Rong, Kaibin; Ding, Han; Chen, Siyu; Wang, Yongsheng; Zhou, Zhenyu; Lu, Riu
Abstract: Focusing on the collaborative manufacturing requiring meshing interface physical performances, an innovative Top-Rem grinding tool modification considering loaded edge contact is proposed for spiral bevel gears. Accurate Top-Rem grinding tool parameters can instead of machine-tool settings and their impact in the sophisticated flank topography correction technique. At first, the whole Top-Rem tool modification includes: i) arc-shaped blade part; ii) Top-Rem part; iii) top fillet part. Then, grinding tool modification model considering both loaded contact and geometric accuracy is established. Where, three important constraint conditions were taken into accounts: i) geometric boundary considering loaded edge contact, ii) root overcutting, and iii) flank geometric accuracy. Moreover, two kinds of optimization strategies are proposed to improve the accuracy and efficiency of the whole modification: i) two types of modification by the different tool modification parameters; ii) sensitivity analysis with respect to ease-off for optimization operation of the unknown variables. Finally, the given instances can verify that it can get accurate and effective loaded contact performance optimization in early stage of full life cycle product development.